2017
DOI: 10.1002/hed.24718
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient health engagement with mobile texting: A pilot study in the head and neck postoperative setting

Abstract: Background Cell phone ownership is nearly universal. Messaging is one of its most widely used features. Texting-based interventions may improve patient engagement in the post-operative setting, but remain understudied. Methods Patients were recruited before discharge and received automated daily texts for one week, providing information about expected recovery. Patients were encouraged to text questions to providers, which were triaged for intervention. Web-based surveys solicited patient feedback about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 21 publications
0
24
0
2
Order By: Relevance
“…PGHD have the potential to change the paradigm for existing normal ranges [ 2 ]. Information gathering through patient health platforms is expected to benefit medical care and patient health outcomes [ 9 - 14 ]. Meanwhile, there are concerns about the construction of such patient health platforms [ 10 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…PGHD have the potential to change the paradigm for existing normal ranges [ 2 ]. Information gathering through patient health platforms is expected to benefit medical care and patient health outcomes [ 9 - 14 ]. Meanwhile, there are concerns about the construction of such patient health platforms [ 10 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…smartphone apps and an Internet-based program for mental health management,[47 48] and a text-messaging tool to improve postoperative care [49]. Measures of use in these studies included any use of the tools and frequency of interactions with the tools.DISCUSSIONIn this review of recent evidence, we found only 29 studies evaluating use by patient characteristics.…”
mentioning
confidence: 99%
“…Former discharge letter interventions intended to improve information flow between hospitals and general practitioners [ 8 – 10 ]. Recently, with the evolving concept of patient-centred communication, discharge information increasingly aims to address the patient directly, also with the help of modern technology such as reminders sent to the patient via short message service [ 11 13 ], or letters sent electronically thus entirely replacing the conventional paper-based transmission [ 14 , 15 ]. It could be demonstrated that patient-directed discharge information significantly improved patient understanding of the reason for hospitalisation and post-discharge recommendations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%